Flexoelectric MEMS: towards an electromechanical strain diode. Issue 3 (17th December 2015) - Bhaskar, U. K.; Banerjee, N.; Abdollahi, A.; Solanas, E.; Rijnders, G.; Catalan, G.
Abstract : Ferroelectric nanocantilevers function as switchable "strain diodes": their electromechanical response is enhanced when ferroelectricity and flexoelectricity are parallel, and diminished or even suppressed when they are antiparallel. Abstract : Piezoelectricity and flexoelectricity are two independent but not incompatible forms of electromechanical response exhibited by nanoscale ferroelectrics. Here, we show that flexoelectricity can either enhance or suppress the piezoelectric response of the cantilever depending on the ferroelectric polarity and lead to a diode-like asymmetric (two-state) electromechanical response.